Pengelolaan dan Pencegahan Middle East Respiratory Syndrome (MERS) - Kartika, Ronald Winardi; Kwary, Meilyana Maria Isabela; bt Mohamad, Haznawi; b. Sazali, Muhamad Shazwan; bt. Muhamad Nasir, Nurainaa Ayuni; b. Che Rani, Muhammad Aiman Afiq (PT. Kalbe Farma Tbk., 2017)
Middle East Respiratory Syndrome (MERS) adalah penyakit yang disebabkan oleh MERS-Coronavirus (MERS-CoV). Umumnya, MERS menyebabkan gejala sistem pernapasan seperti batuk, sesak napas dan demam. Saat ini tiada pengobatan khusus untuk MERS. Ribavirin dan interferon-Î±2a yang digunakan untuk mengobati penyakit akibat coronavirus dapat membantu mengobati MERS.Middle East Respiratory Syndrome (Mers) is a disease caused by MERS-Coronavirus (Mers-CoV). Generally, MERS causes respiratory symptoms such as cough, shortness of breath and fever. There is no specific treatment for MERS. Drugs used to treat diseases caused by coronavirus such as ribavirin and interferon-Î±2a can be used.